PERILAKU BISNIS PETANI DALAM USAHATANI BERAS SEMI ORGANIK DI KECAMATAN PANDAK KABUPATEN BANTUL - Arif Hermawan; Roso Witjaksono; Harsoyo Harsoyo (Agro Ekonomi, 2015)
This research aimed to know farmer s business behavior in semiorganic rice farming and also to know factorswhich influence it. This research was using descriptive analytic method by survey technique. Subdistrict, villages,andfarmer group/association offarmer group samples were chosen by purposive method. 60 group member samples were taken from every farmer group/association offarmer group sample by proportional random sampling. Data was analized by Proportion Test and Multiple Linear  Regression Analysis.The result of research shows that most of farmers have good business behavior in semiorganic rice farming. Business knowledge, role of farmer group leader, and farmer activity in extension give positive influence to farmer business behavior, while motivation, income alocation, working experience, type of business information resources, and outside capital do not influence its business behavior in semiorganic rice farming.